Cerebrospinal Fluid Concentrations of Nimodipine Correlate With Long-term Outcome in Aneurysmal Subarachnoid Hemorrhage: Pilot Study. Issue 5 (September 2019) - Riva, Roberto; Pegoli, Marianna; Contin, Manuela; Perrone, Alessandro; Mohamed, Susan; Zanello, Marco
Abstract : Objectives: The aim was to evaluate plasma and cerebrospinal fluid (CSF) nimodipine concentrations in patients with aneurysmal subarachnoid hemorrhage and their correlation with clinical outcome. Methods: Nimodipine infusion was started at 1 mg/h and increased up to 2 mg/h and continued up to 21 days in surviving patients. Arterial and CSF samples were collected at least after 24 hours of stable nimodipine dosing. Delayed cerebral ischemia and vasospasm were documented by new neurological deficits and neuroimaging. The clinical outcome was assessed at 9 months by the modified Rankin scale. Results: Twenty-three patients were enrolled. Nimodipine dose was 13 to 38 μg/kg per hour. Nimodipine arterial and CSF concentrations were 24.9 to 71.8 ng/mL and 37 to 530 pg/mL, respectively. Dose did not correlate with arterial or CSF concentrations. Arterial concentrations did not correlate with corresponding CSF concentrations. Doses and arterial concentrations did not correlate with the clinical outcome and were not associated with the occurrence of delayed cerebral ischemia. However, patients with no significant disability after 9 months of hemorrhage showed significantly higher CSF nimodipine concentrations ( P = 0.015) and CSF-to-plasma ratios ( P = 0.011) compared with patients who showed some degree of disability or who died. Conclusions: Cerebrospinal fluid nimodipine concentrations measured during hospital drug infusion showed a correlation with long-term clinical outcome in patients with aneurysmal subarachnoid hemorrhage. These very preliminary data suggest that CSF concentrations monitoring may have some value in managing these patients.